'Welcome to the Atrocity Exhibition': Ian Curtis, Rock Death, and Disability - Church, David (Disability Studies Quarterly, 2006)
Since the 1960's, rock music's countercultural aesthetic has willingly and exploitatively appropriated images and cultural attitudes equating disability with freak show spectacle, linking the figure of the self-destructive rock star to the supposedly tragic and socially ostracized "freak." This tendency manifests itself in many forms, from "freakish" concert performances (e.g., heavy metal acts using persons with disabilities as part of their live stage show) to the excessive mythologizing of dead rock stars. The life of Ian Curtis, singer of the seminal post-punk band Joy Division, provides a useful case study for how ableist values have permeated rock music, metaphorically conflating rock stardom with freakery in potentially negative ways for actual persons with disabilities. There currently exists very little scholarship on disability in popular, non-classical music, but I hope this essay will encourage further work.